Podnikové obligace, či podnikové dluhopisy? - Tetřevová, Liběna (Univerzita Pardubice, 2000)
The article deals in detail with the term corporate bond. Corporate bonds represent long-term, wholesale issuing, marketable, debt securities, issued by business units. They claim the obligation of the issuer to pay interest payments and principal to the bondholders on specific dates. Some authors confuse the term bond and the term promissory note and bill. We can summarize the following: corporate bonds represent the type of promissory notes tohether with bills and other specific forms of promissory notes.
Keywords: cenné papíry; pojmy; dluhopisy; dlužní úpisy; obligace; směnky